Individual evaluation vs fact-checking in the recognition and willingness to share fake news about COVID-19 via Whatsapp - Brenes Peralta, Carlos Manuel (2021)
The aim of the study is to research the effects of individual evaluation of fake and truthful news about COVID-19, compared to the exposure to fact-checking on the intention to share them via WhatsApp. An online experiment was conducted with a convenience sample of 819 Costa Ricans. Results show that people in the individual evaluation condition assess completely fake news with greater veracity and completely truthful information with less veracity, compared to the fact-checking condition. This response is more pronounced in the most religious people and among those most affected by structural inequalities in Costa Rican society (e.g., lower educational level, living on the coasts and lower subjective income). Finally, both the individual evaluation of disinformation content and exposure to fact-checking reduce the intention to share fake news about COVID-19 via WhatsApp.